2019
DOI: 10.1039/c9dt03673c
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-gel preparation and ammonia synthesis activity of compounds in the quaternary (Ni,M)2Mo3N (M = Cu or Fe) systems

Abstract: Solid solutions based on copper and iron substitution into the nickel sites of Ni2Mo3N are produced using a citrate gel approach and used to catalyse ammonia synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…A minor N deficiency is common and has been noticed before. 14 In addition, Co, Ni, Fe, and Mo content values (determined by EDX analysis) were close to the expected values (Table S7). Therefore, the bulk character- ization showed that the compositions of nitrides were consistent with the targeted stoichiometries.…”
Section: Synthesis and Characterization Of Nimentioning
confidence: 99%
See 3 more Smart Citations
“…A minor N deficiency is common and has been noticed before. 14 In addition, Co, Ni, Fe, and Mo content values (determined by EDX analysis) were close to the expected values (Table S7). Therefore, the bulk character- ization showed that the compositions of nitrides were consistent with the targeted stoichiometries.…”
Section: Synthesis and Characterization Of Nimentioning
confidence: 99%
“…S2−S6). 14 Meanwhile, Mo and N (located on 12d and 4a positions) are always fully occupied and unaffected by Fe-substitution.…”
Section: Synthesis and Characterization Of Nimentioning
confidence: 99%
See 2 more Smart Citations
“…[84] (Table 3, Entry 5-6) Unlike Co 3 Mo 3 N (η-6 carbide structure), Ni 2 Mo 3 N crystallizes in β-Mn structure with low extent of lattice N exchange, hence lower activity in comparison to Co 3 Mo 3 N. [84] Additionally, partial substitution Co, Cu and Fe at the nickel sites in Ni 2 Mo 3 N has no major influence on the electronic properties hence no enhancement in NH 3 synthesis rate. [91] ( Table 3, Entry 7-10) Preliminary studies reported antiperovskite nitrides (Co 3 ZnN, Ni 3 ZnN, Co 3 InN, and Ni 3 InN) can produce NH 3 in H 2 /Ar atmosphere. Lattice N of these compounds are converted to into NH 3 , but further regeneration of lattice N was not realized and advanced research is necessary to efficiently produce NH 3 with long life.…”
Section: Ni 2 Mo 3 N(2-3-1) With Different Compositions Than Co 3 Mo mentioning
confidence: 99%